Eugeniusz Piasecki’s concept of winter sports in view of modern PE objectives and the Olympic idea - Makuła, Waldemar (Akademia Wychowania Fizycznego w Poznaniu)
The article aims to initiate a wider discussion on the development of Polish sport in association with physical education of children and youth, which would take into account the achievements of its pioneers. The study focuses first on the pioneering concept of a Polish physical education theorist, Eugeniusz Piasecki, based on application of different sports, including winter disciplines, in the physical education of children and adults. Piasecki’s approach was not only innovative but it also involved many valid postulates in the context of current proposals to promote sports lifestyles in society. The realization of these postulates is hardly possible without the proper involvement of physical education. Focusing on gaining expected results in his pedagogical practice, Piasecki did not limit possible problem solutions to his own initiatives, but first analysed different approaches to physical education in Europe and North America and then compared them with the situation of physical education and sport in Poland. The analysis of Piasecki’s concept indicates the still current but only partially implemented proposals for development of sport in its relationship with the Olympic idea in Poland
Keywords: Olympism; physical education; winter sports